2021
DOI: 10.3390/s21134438
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Sensor Technology for Balance Assessment in Home Rehabilitation Settings

Abstract: The increased use of sensor technology has been crucial in releasing the potential for remote rehabilitation. However, it is vital that human factors, that have potential to affect real-world use, are fully considered before sensors are adopted into remote rehabilitation practice. The smart sensor devices for rehabilitation and connected health (SENDoc) project assesses the human factors associated with sensors for remote rehabilitation of elders in the Northern Periphery of Europe. This article conducts a lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Most research on wearable sensor technologies currently places accuracy at the center of the design. This often comes at the expense of usability, which can ultimately have negative effects on continued device use [ 6 ]. Previous research suggests that, to achieve successful adoption of remote rehabilitation technologies, the solution must be both practical and usable [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research on wearable sensor technologies currently places accuracy at the center of the design. This often comes at the expense of usability, which can ultimately have negative effects on continued device use [ 6 ]. Previous research suggests that, to achieve successful adoption of remote rehabilitation technologies, the solution must be both practical and usable [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, most research on wearable sensor technology is developed with accuracy at the center of the study design. This often comes at the expense of usability [ 6 ] even though research studies have indicated that perceived ease of use is just as important as perceived usefulness when it comes to technology acceptance [ 7 ]. Indeed, Mancini and Horak [ 8 ] note that, to achieve successful adoption of remote rehabilitation technologies, the solution must be both practical and usable, which is of particular importance when considering wearable sensor systems.…”
Section: Introductionmentioning
confidence: 99%
“…Kelly et al [32] discussed the importance of accurate and objective clinical balanceassessment methods. A review was conducted on the state of the art related to technologyenabled balance-assessment methods and their potential to be utilised in remote rehabilitation settings.…”
Section: Applicationsmentioning
confidence: 99%
“…Wearable sensors have the characteristics of convenience and a low price, providing researchers with a variety of possibilities and solutions [ 11 ]. Wearable sensors help rehabilitation patients to exercise at home, relieve travel pressure, and reduce psychological burden [ 12 , 13 ]. A variety of sensing devices are used to monitor patients’ vital signs and physiological responses, such as electromyography (EMG), electrocardiogram (ECG), and electroencephalogram (EEG), which can monitor the patient’s physical condition in real time.…”
Section: Introductionmentioning
confidence: 99%